The Settlement Network in Spatial Plans in the Republic of Serbia – Key Dilemmas - Živanović, Zora; Popović, Vladimir (Geographica Pannonica, 2026)
The settlement network represents one of the key segments of spatial plans in Serbia, as well as part of the broader framework that encompasses the population and public services within a given territory. The ways in which this segment has been addressed in practice show considerable variation, which points to the absence of a clearly established and widely accepted approach. This paper presents a comparative analysis of spatial plans at the national, regional, and local levels, with the aim of examining the methodological and substantive consistency in the treatment of this segment, as well as the degree to which individual subsegments and related concepts are included. The results of the research made it possible to identify key uncertainties and inconsistencies, which may serve as a basis for improving planning practice, that is, for enhancing its quality and relevance in the planning of settlement network development.